Theaflavin 3, 3′-Digallate Delays Ovarian Aging by Improving Oocyte Quality and Regulating Granulosa Cell Function. (8th December 2021) - He, Jiahuan; Yao, Guidong; He, Qina; Zhang, Tongwei; Fan, Huiying; Bai, Yucheng; Zhang, Junya; Yang, Guang; Xu, Ziwen; Hu, Jingyi; Sun, Yingpu
Abstract : Ovarian aging refers to the gradual decline of ovarian function with increasing physiological age, manifested as decreased ovarian reserve, elevated aging-related markers, and reduced oocyte quality. With a declining female fertility and a growing aging population, it is urgent to delay ovarian aging to maintain fertility and improve the life quality of women. Theaflavin 3, 3 ′ -digallate (TF3) is a naturally bioactive polyphenol compound extracted from black tea, and its antioxidant properties play an important role in maintaining human health and delaying aging; however, the effects of TF3 on female reproduction and ovarian function are not yet clear. Here, we show that TF3 can preserve primordial follicle pool, partially restore the estrous cycle, and increase the offspring number of aged mice. Meanwhile, TF3 gavage increased the number of oocytes retrieved, decreased the level of reactive oxygen species, increased the level of glutathione, and decreased the abnormal rate of oocyte spindle after ovulation induction. Moreover, TF3 inhibited human granulosa cell apoptosis and improved their antioxidative stress ability. High-throughput sequencing and small-molecule-targeted pharmacological prediction show that TF3 affects multiple pathways and gene expression levels, mainly involved in reproductive and developmental processes. It may also affect cellular function by targeting mTOR to regulate the autophagic pathway, thereby delaying the process of ovarian aging. This study shows that TF3 can be used as a potential dietary supplement to protect ovary function from aging and thereby improving the life quality of advanced-age women.